ROLE OF LAW ENFORCEMENT AGENCIES IN THE IMPLEMENTATION OF THE NATIONAL SECURITY STRATEGY IN UKRAINE (1991 – 2014) - VYHIVSKYI, Ivan; ONDRIAŠ, Juraj (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the study is to analyze the current legislation of Ukraine in the context of the system formation for ensuring national security of Ukraine, to identify the role of law enforcement agencies in building the national security strategy, and to study the main areas of legal regulation of the law enforcement agencies activities in this area. The Methodology of the Research. In the study there have been used general scientific and special methods, in particular, owing to the historical legal method, the conceptual principles in interpreting the concept of national security and law enforcement agencies have been revealed, the legislation has been analyzed; systemic structural and formal logical methods have been applied. The scientific novelty: the areas of activity of law enforcement agencies as subjects of the national security system of Ukraine have been analyzed, and the directions of state policy implementation in this area have been outlined. The Conclusions. Based on the analysis of the legislation of Ukraine during the period of 1990 – 2014, it has been stated that the national security system is a set of subjects of ensuring national security, which united common goals regarding the interests of the state and society. The fundamental state-forming documents of the 1990s outlined a set of identical concepts related to national security. The specification of threats in the field of national security, and therefore the creation of more effective directions of state policy, took place at the beginning of the 2000s and the adoption of the first two National Security Strategies in 2007 and 2012. However, their excessive declarativeness, terminological overload partially improved the practical activities of security subjects. The activities of law enforcement agencies in this area are mainly the protection of citizens' rights and freedoms, the state and public interests from unlawful encroachments, ensuring security. It has been determined that during the specified period, the activities of law enforcement agencies in the field of national security required coordination of various branches of legislation, the adoption of special legislation. It has been noted that such specific steps towards developing a new national security strategy with a clearer and more systematic regulatory framework took place after 2014: a number of innovations were adopted that update the systemic development of security and defense sector, which also include law enforcement and intelligence agencies. Keywords: law enforcement agencies, national security, Ministry of Internal Affairs, Security Service of Ukraine, entities ensuring national security.